MAJOR LYMPHOCYTE SUBPOPULATIONS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND THEIR ASSOCIATIONS WITH CELLULAR AND HUMORAL ANTI-ENDOTOXIN IMMUNITY - D. V. Shaduro; V. A. Beloglazov; A. I. Gordienko (Медицинская иммунология)
At the present time, systemic lupus erythematosus (SLE) takes the leading place among systemic autoimmune disorders. Despite considerable progress in understanding basic pathogenesis of this disease, many subtle mechanisms of progressive inflammation in SLE are still unknown. It has been discovered that the persistent self-maintenance factors of autoimmune inflammation could be represented by lipopolysaccharides or endotoxins of Gram-negative intestinal bacteria. The objective of this study was to assess the levels of major lymphocyte subpopulations, and their probable relation to specific anti-endotoxin antibodies and endotoxin-neutralizing receptors of granulocytes and monocytes in peripheral blood of SLE patients. The study involved forty-eight patients with SLE. The levels of lymphocyte subpopulations, expression of monocyte and granulocyte anti-endotoxin receptors, amounts of total and endotoxin-specific immunoglobulins were determined by means of, respectively, cytometric analysis and enzyme immunoassay techniques. The results of study have shown an increase in overall numbers of activated and cytotoxic T lymphocytes, a decrease in lymphocytes and NK-cells, diminished levels endotoxin-binding receptors on the monocytes and granulocytes, along with increased anti-endotoxin IgG antibodies. Our study revealed correlations between the levels of the leukocyte endotoxin-binding receptors, and B-lymphocyte contents, like as some associations between anti-endotoxin IgM antibodies, and the levels of B-lymphocytes, and cytotoxic T-lymphocytes. A correlation was also found between anti-endotoxin IgG antibodies and CD4+ lymphocyte levels. Significant alterations of the endotoxin-specific immunity among SLE patients suggest that this imbalance might play an important role in the mechanisms of onset and progression of autoimmune diseases.